Paper 4: Mechanical Properties of Bricks of the Coudenberg Archaeological Site in View of a Proper Conservation Strategy. (February 2014) - De Clercq, Hilde; Fontaine, Laurent; Hayen, Roald; Godts, Sebastiaan
<x content-type="archive" xml:space="preserve">Abstract</x> Archaeological sites are essentially submitted to decay phenomena inherent on their history as well as the environment to which they are exposed after excavation. The history of such archaeological sites is particularly related to their long-term underground conservation conditions during which they were subject to salt migration into the architectural remains. This paper describes the results of drill resistance measurements using a drill resistance measurement (DRMS) device to evaluate the mechanical damage resulting from salt crystallization pressures. Further tetraethoxysilane (TEOS) was applied on powdered bricks of often moist archaeological remains. It was noticed that TEOS serves as potential nutrient for present moulds. The mechanical consolidation effect was evaluated by comparing the hardness profiles after treatment with the reference ones. Bricks used for the construction of the Aula Magna, situated underneath the Royal Square, are characterized by severe patterns of fissures for which the damage diagnosis was built up.